ID 214 – Optical coherence tomography and multifocal visual evoked potentials usefulness to detect visual pathway abnormalities in clinical practice. Issue 3 (March 2016) - Guerrieri, S.; Maggio, G. Di; Vitali, F.; Santangelo, R.; Medaglini, S.; Moiola, L.; Carro, U. Del; Martinelli, V.; Comi, G.; Leocani, L.
Abstract : Objective: Full-field visual evoked potentials (ff-VEP) are fundamental in neurological practice to define the nature of visual disturbances. We explored whether, in case of normal ff-VEP and suspected organic visual pathway involvement, multifocal visual evoked potentials (mf-VEP) and optical coherence tomography (OCT) can be useful in the diagnostic workup. Methods: Observational case reports. Results: Three patients arrived at our department for visual disturbances. Two had relapsing optic neuritis (ON) and visual acuity (VA) loss, with normal or non-significant ff-VEP outside acute clinical episodes. In both cases OCT showed a retinal nerve fiber layer (RNFL) thickness reduction, allowing visual pathway damage identification. The third, with meningioma involving left optic nerve, complained of blurred vision in the nasal field of the left eye as confirmed by computerized perimetry (CP). While ff-VEP showed normal latency and non-significant amplitude reduction in the left eye, mf-VEP showed important amplitude reduction in the whole lower left eye field. OCT scan confirmed axonal damage showing left RNFL thinning. Conclusions: Sometimes ff-VEP fails in identifying abnormalities in patients with processes involving the visual pathway, particularly in cases with axonal or sectoral optic nerve involvement. We suggest the importance of a multimodal evaluation, including OCT and mf-VEP.